Clinicopathological study of urinary bladder tumors. Clinical evaluation of immunohistochemistry in urine cytology - Nagata, Y (Hinyokika kiyo. Acta urologica Japonica, 1985)
We report on the immunohistochemical detection of carcinoembryonic antigen in the urine cytology of 5 patients with urinary bladder tumors classified as low, moderate, and high grade. Immunohistochemically carcinoembryonic antigens were detected in urine cytology in the case of moderate and high grade tumors, but not, low grade tumors. Carcinoembryonic antigen positivity in urine cytology correlated with the histological grade of a bladder tumor. Carcinoembryonic antigen in urine cytology seemed to be a potentially good marker to distinguish between high grade and low grade tumors